Chomsky : ideas and ideals - Smith, Neil (Cambridge University Press, 1999)
Noam Chomsky is one of the leading intellectual figures of modern times. He has had a major influence on linguistics, psychology and philosophy, and a significant effect on a range of other disciplines froma anthropology to mathematics, education to literary criticism.